Awareness of postpartum depression among midwives and pregnant women in Arkhangelsk, Arctic Russia - Elena Nechaeva; Olga Kharkova; Vitaly Postoev; Andrej M. Grjibovski; Elisabeth Darj; Jon Øyvind Odland (Global Health Action)
Background Postpartum depression (PPD) affects approximately 17% of the women worldwide with nearly half of all cases going undetected. More research on maternal mental health, particularly among healthcare professionals and pregnant mothers, could help identify PPD risks and reduce its prevalence. Objective Given that awareness of PPD is a crucial preventive factor, we studied PPD awareness among midwives and pregnant women in Arkhangelsk, Arctic Russia. Methods A qualitative study was conducted using in-depth semi-structured interviews. Midwives and pregnant women were recruited from the women’s clinic of the Arkhangelsk municipal polyclinic. Seven midwives and 12 pregnant mothers were interviewed. Results Midwives described limited time for psychological counselling of pregnant women; they reported that their primary focus was on the physiological well-being of women. Pregnant women have expressed a desire for their families to share responsibilities. The participants considered PPD as a mix of psychological and physiological symptoms, and they also highlighted a discrepancy between the expectations of pregnant women and the reality of motherhood. The present study underscored the limited understanding of PPD identification. Conclusions The findings suggest that there is a need for increased awareness among midwives and pregnant women regarding PPD. Prevention programs targeting PPD with a specific emphasis on enhancing maternal mental health knowledge are warranted.